Staphylococcus aureus resistentes a meticilina (SARM) y productores de enterotoxina A aislados de portadores nasales asintomáticos entre estudiantes universitarios de México - Adame-Gómez Roberto; Vences-Velázquez Amalia; Parra-Rojas Isela; Rodríguez-Bataz Elvia; Muñoz-Barrios Salvador; Ramírez- Peralta Arturo (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2019)
Abstract: The aim at this study was determine the frequency of S. aureus, including methicillin-resistant and enterotoxin A production in nostrils of university students in Mexico. This was a cross-sectional study conducted in 471 university students from a city in southwestern Mexico. Nasal samples and sociodemographic data were obtained from the patients. Strains were identified as S. aureus based on morphology, Gram stain, catalase test, coagulase test and fermentation on salted mannitol agar. Isolated strains were subjected to biotyping, their methicillin resistance was analyzed using the agar diffusion method and examined their enterotoxin A (SEA) production by a Dot-blot analysis. The nasal carriage rate of S. aureus was 10.40%; 73.46% of the isolates were resistant to methicillin; 36.73% of the strains produced enterotoxin A. In the bivariate analysis, a statistically significant difference was found in patients who lived near sewage and farms with S. aureus carriage (p=0.012, odds ratio 2.59, [ 1.06-5.81]; p=0.009, odds ratio 3.18, [1.07- 8.33]) and the first group also associated with methicillin resistant S. aureus carriage (p=0.020, odds ratio 3.38, [1.30-8.06]). Nasal carriers show a wide variety of strains of S. aureus, mostly MRSA strains, but not all produce enterotoxin A. Resumen: El objetivo de este estudio fue determinar la frecuencia de S. aureus, incluyendo resistentes a meticilina y la producción de enterotoxina A en fosas nasales de estudiantes universitarios en México. Este fue un estudio transversal realizado en 471 estudiantes universitarios de una ciudad del suroeste de México. Las muestras nasales y los datos sociodemográficos fueron obtenidos de los pacientes. Las cepas fueron identificadas como S. aureus basándose en la morfología, tinción de Gram, prueba de catalasa, prueba de coagulasa y fermentación en agar manitol salado. Las cepas se biotipificaron, se determinó la resistencia a meticilina por difusión en agar y la producción de enterotoxina A por Dot- Blot. La frecuencia de portadores nasales de S. aureus fue 10,40 %; 73,46 % resistentes a meticilina; 36,73 % producen enterotoxina A. En un análisis bivariado, se encontraron diferencias estadísticamente significativas en pacientes que viven cerca de aguas residuales y granjas con el estado de portador de S. aureus, (p=0,01, OR 2,59 [1,06-5,81]; p=0,01, OR 3,18, [1,07- 8,33]). Los portadores nasales muestran una diversidad de cepas de S. aureus, mayormente resistentes a meticilina, pero no todas producen enterotoxina A.